Supercritical Fenton Oxidation: A New Method for Total Organic Carbon Measurement. (3rd May 2017) - Fang, Lin; Hu, Huanjie; Lin, Chunmian
ABSTRACT: A new method for total organic carbon (TOC) measurement was established based on supercritical Fenton oxidation. The organic pollutants in wastewater were oxidized to carbon dioxide in supercritical water by Fenton reagents that was detected using a nondispersive infrared detector. The influence of temperature from 380 to 480°C, oxidant coefficient from 1 to 20, pH from 2.2 to 5.2, and Fe 2+ concentration from 0.2 to 0.8 mg L −1 was characterized; the optimal conditions were at 420°C, an oxidant coefficient n ≥ 5, a pH of 4.4, and Fe 2+ concentration of 0.8 mg L −1 . Using these parameters, the recovery of potassium hydrogen phthalate exceeded 98.2%. The introduction of Fenton oxidation based on supercritical water lowered the temperature and reduced the oxidant coefficient required for TOC determination.